Report of deputation to Minister of Health on "A National Health Service"...
1945-03 1945 1940s 8 pages -3- The Ministers and their colleagues had an opportunity of doing a very great job in a very great way and he was sure that posterity would be grateful if it succeeded. The Trade Union Movement appreciated that the White Paper was a very big step forward. There were, however, some reservations to be made. The first assurance they would like was that nobody would be allowed to contract out of the new health scheme. Numerous people were contributing to hospital schemes but it was essential that nobody, for any reason, should be allowed to contract out of the scheme. Once that happened the scheme in general would be very decidedly weakened. It was also necessary that an assurance be given that in the operation of the new health scheme no provision should be made by which private practice would be superior in any way to the public service. That was of the utmost importance to the success of the scheme. Not only the medical and surgical services in relation to illness should be provided under the scheme but also people should be prevented from becoming ill. Prevention should be the aim. There was an urgent need for a large number of doctors to make the health service a success. The T.U.C. felt that education should be free so that anyone who was looked upon as the right kind of person to become a doctor should have that opportunity provided. The question as to whether the new measures in the Education Act would help was a matter of opinion but they thought that they might. The T.U.C. had had meetings with the B.M.A. and an idea had been gained as to their approach to the question of a National Medical Service. Quite naturally a profession of their standing recognised everywhere in the world was a little jealous of interference from any quarter but there was one point upon which one could sympathise with the B.M.A. and that was that whether it be the remuneration or other conditions of service, they should be adequate in every way to attract and retain the best type of personnel into the public service. Young doctors required an opportunity for study leave and higher degrees and those facilities should be provided for the young doctor who might be on the salaried list of the Ministry just as easily as they were provided for anyone who took a private practice. Every step should be taken to build up a first class service. The General Council did not want to see the public part of the service suffer if a doctor was a party to both public service and private practice. That was in no sense an accusation against any member of the medical profession but in a big new scheme of the kind envisaged it was essential to retain public confidence and that would be damaged if only a few people took advantage of the fact that they were on the pay roll of the State and had a private practice as well. That position had to be guarded against, but the Minister was probably conversant with that danger. In reference to Rehabilitation Mr. Allen said that the T.U.C. had for something like ten years been advocating it and trying to popularise it. Unfortunately it had taken a great war to bring it into prominence and now a limited number of people in the medical profession were supporters of rehabilitation. It had been a little frightening at meetings with the Ministry of Labour on the question of disabled persons to hear the statement made that "even doctors do not understand rehabilitation". That 292/847/3/118